A Study of SWAYAM Prabha DTH TV Channel (Kishore Manch) in Secondary and Senior Secondary Schools of India - Kumar, Abhay; Gupta, Deepty; Behera, Amarendra (JOURNAL OF INDIAN EDUCATION, 2022)
Technology undergoes constant evolution. As newer technologies emerge, they absorb and integrate the capabilities of the outgoing ones. However, this doesn’t render the earlier technologies obsolete. They persist and can be utilised to achieve valuable educational outcomes. The objectives of both technology and education align in a way that fosters synergies, enhancing children’s learning experiences. Television, a technology that continues to endure, possesses unique features. Combining both audio and visual elements, it stands out as a powerful tool for delivering diverse information effectively. Educational television, in particular, serves as a crucial device for disseminating education widely among the masses. In this paper, the awareness, accessibility and perception of Swayam Prabha DTH TV Channel ‘Kishore Manch’ was studied across various States/UTs of the country using both qualitative and quantitative data. The results indicated that there was limited awareness about the channel. Accessibility of the channel in the sampled States/UTs is still a challenge. The perception of teachers towards the channel was positive but there is a scope of improving the production quality of educational programmes. Additionally, challenges such as discontinuity in series telecast need addressing, along with the endeavour to captivate students’ interest in DTH TV. As the efforts are underway to expand the initiative of educational TV in India, the paper seeks to discuss the results of the surveys about this expansion.